The Assossiation Between Stress During the COVID-19 Pandemic and the Incidence of Dyspepsia Syndrome in The First Year Medical Students - Rahmi, Wahida; Yulistini, Yulistini; Murni, Arina Widya (UI Scholars Hub, 2022)
Introduction. Dyspepsia syndrome is a collection of symptoms in the upper digestive tract associated with dysregulation of the hypothalamus-hypophysis axis that is triggered by stress. One of the problems faced in the world today is the COVID-19 pandemic which can be a new stressor, especially for students with many changes in the learning process. This study aimed to examine the relationship between stress during the COVID-19 pandemic and the incidence of dyspepsia syndrome.Methods. An analytic obsevasional with cross-sectional design was conducted in April-June 2021 at the Faculty of Medicine, Andalas University. The subjects of this study were the first batch of medical students which were selected by total sampling. Level of stress was measured using a questionnaire adapted from DASS-42, meanwhile dyspepsia syndrome was examined using ROME IV questionnaire. Bivariate analysis was conducted by using Chi-square and Fisher exact test.Results. 68 of 238 students experienced stress with the most stress levels was mild-moderate stress (85.3%) and severe-very severe stress (14.7%). There were 44 students who experienced dyspepsia syndrome from a total of 68 respondents (64.7%). There was no relationship between stress and the incidence of dyspepsia syndrome (p=1,00). However, child’s status were found to be a risk factor for stress stres [p=0.006; OR=13.46 (95%CI 2.134-84.894)].Conclusions. There is no significant relationship between stress during the COVID-19 pandemic and the incidence of dyspepsia syndrome in first-year medical students. However, the results of this study indicate that first child status is a risk for stress to dyspepsia.